Boosting of activity enhancement of K+-responsive quadruplex hammerhead ribozyme. Issue 27 (2nd March 2015) - Yamaoki, Yudai; Mashima, Tsukasa; Nagata, Takashi; Katahira, Masato
Abstract : Second-generation quadruplex hammerhead ribozymes, whose activity enhances in response to K +, were developed. New strategies suppressed the basal activity and boosted the activity enhancement upon the addition of K + to 21-fold. Abstract : Two second-generation quadruplex hammerhead ribozymes, whose activity enhances in response to K + via quadruplex formation of embedded r(GGA)3 GG, were developed. Different strategies were applied to suppress basal activity when K + is absent. As a result, the activity enhancement upon the addition of K + has reached as high as 21-fold.